PENGARUH VARIASI WAKTU GESEK PADA PENGELASAN GESEK (FRICTION WELDING) TERHADAP KEKUATAN IMPAK BAJA ST37 - Ardi Meilianto; Rodika Rodika; Muhammad Rivai (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Friction welding is a method of reasoning that is carried out to obtain welds by rubbing the ends of two workpieces. so that the contact surface will be hot, and the metal surface in the area becomes liquid. In these hot conditions, the friction between the two metals is stopped, resulting in a welded joint. The purpose of this study was to determine the effect of variations in friction time on the impact strength of the friction welding process on ST37 steel. ST37 steel used is a solid cylinder with a diameter of 13mm. This study uses an experimental method, with variations in the friction time of 4 minutes, 5 minutes. and 6 minutes with a speed of 720 rpm, and a distance of 3 mm pressing. From this research, it was found that welding with a friction time of 6 minutes produced the highest value for the absorbed energy of 49.73 joules, and for the impact value of 1.740 joules/mm², while the lowest value was at a friction time of 4 minutes with the energy values ​​being absorbed is 32.03 joules, and the impact price is 1.119 joules/mm².